Good practices of cocoa production in communities victims of the conflict, Granada (Colombia). (Revista Sistemas de Producción Agroecológicos, 2020)
The objective of this project was aimed at being able to contribute as an institution to the progress of the communities victims of the armed conflict, which in past decades were forced to participate in the production of illicit crops due to the limited income alternatives in the area; for this reason, the development of this project took place in the middle Ariari area, in the Granada municipality of the Meta department, where the beneficiary population has cocoa cultivation that does not exceed five hectares per producer. Therefore, 50 people from populations victims of the conflict, peasants and women were trained; in processes such as processing and transformation of cocoa, seeking to strengthen this production chain because it is a desired product for chocolate industries at the level and the foreign market. A training called “cocoa production processes” was designed, which included stages from harvesting the pods to obtaining different agro-industrial products that generate income for farm families and boost the economy of the sector. This training was subdivided into 6 sub-conferences: Cocoa processing, transformation of cocoa into table chocolate, facilities of a cocoa transformation plant, equipment necessary for cocoa transformation, obtaining of cocoa liquor and agroindustrialization alternatives, where it was obtained active participation by the fifty attending producers, great acceptance and willingness in the topics taught, which shows the interest that this type of activity generates for the populations that contribute to the development of the region.
Keywords: Ariari Colombia; cocoa; armed conflict; agro-industry